2021
DOI: 10.1016/j.jvscit.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of deep femoral artery aneurysm complicated by deep vein thrombosis and pulmonary embolism

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Regardless of the presence of LDS, DFAAs rarely develop and account for 0.5% to 2.6% of all femoral aneurysms. 7 , 9 , 13 In the present report, we have described the case of a patient with LDS and DFAA. To the best of our knowledge, no study has reported the association of DFAAs with LDS.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Regardless of the presence of LDS, DFAAs rarely develop and account for 0.5% to 2.6% of all femoral aneurysms. 7 , 9 , 13 In the present report, we have described the case of a patient with LDS and DFAA. To the best of our knowledge, no study has reported the association of DFAAs with LDS.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have reported that DFA reconstruction might not always be necessary. 9 , 10 We performed DFA reconstruction to reduce the possibility of limb ischemia. We were also concerned about the occurrence of other new peripheral artery disease in the future, such as popliteal artery aneurysms, because of the LDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAAD occurs in three to five out of every 100,000 individuals in the population per year, with a mortality rate of 1-2% per hour. In our current aging society, octogenarians are increasingly undergoing surgery for AAAD [ 1 , 2 ]. Furthermore, elderly patients often have more comorbidities and greater frailty.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 The diagnosis can be difficult until the DFA has expanded, at which point the DFAA will have a high risk of rupture and thromboembolism. 3 …”
mentioning
confidence: 99%